K̨̄ongthun Mūbān : phon kāndamn̄œn ngān ch̄œng khunnaphāp - Manūn S̨̄onk̄œt (Samnakngān Khana Kammakān K̨̄ongthun Mūbān læ Chumchon M̄ưang h̄æng Chāt, Samnak Lēkhāthikān Nāyok Ratthamontrī, 2002)
Community development activities of office of community development funds under Secretariat of the Prime Minister, Thailand.